Meaningful Learning Planning through Understanding by Design - Rini Nur Latifah; Elva Nuraina; Siti Nur Handayani (Journal of Education Action Reseach, 2025)
Graduates of vocational high schools are expected to be job-ready, which requires mastery of specific competencies. However, pre-test results indicated low student achievement due to various contributing factors. This study aims to analyze and address low student learning outcomes by designing more structured instruction oriented toward deep understanding through the Understanding by Design (UbD) approach. The research employed a Classroom Action Research (CAR) design conducted in two cycles involving 18 students, with stages consisting of planning, implementation, observation, and reflection. Data were collected through tests and interviews and analyzed using both quantitative and qualitative methods with source triangulation. The results demonstrated an improvement in the average score from 77.65 in Cycle I to 97.50 in Cycle II, with all students exceeding the minimum mastery criteria. The instructional model also enhanced student motivation and engagement in the learning process. Therefore, the discovery learning model integrated with the Understanding by Design framework proved to be effective and relevant in improving teaching and learning processes in vocational education. This study has positive implications for enhancing instructional quality and is relevant as an alternative strategy for meaning-oriented lesson planning.